Internet-Based Asthma Education -- A Novel Approach to Compliance: A case Report - Cindy O'hara; Dilini Vethanayagam; Carina Majaesic; Irvin Mayers (Canadian Respiratory Journal)
Asthma costs Canadians over $1.2 billion per annum and, despite advances, many asthmatic patients still have poor control. An action plan, symptom diary and measurement of peak expiratory flow have been shown to improve clinical outcomes. Effective educational interventions are an important component of good care. However, many rural sites lack not only access to education but physician care as well. It is reasonable, therefore, that an Internet-based asthma management program may be used as an approach. In the present case report, a novel approach that may increase access in these poorly serviced areas is presented. In an Internet-based asthma management program, patients are reviewed by a physician, receive education and are given a unique password that provides program access. Patients record symptoms and peak expiratory flow rates. The present case report shows that a patient can be assisted through an exacerbation, thus averting emergency intervention and stabilizing control, even when travelling on another continent.